2017
DOI: 10.1021/acs.bioconjchem.7b00153
|View full text |Cite
|
Sign up to set email alerts
|

Targeting and Internalization of Liposomes by Bladder Tumor Cells Using a Fibronectin Attachment Protein-Derived Peptide–Lipopolymer Conjugate

Abstract: A synthetic peptidolipopolymer conjugate, incorporated into liposomes to promote specific binding to the fibronectin (FBN) matrix surrounding bladder tumor cells and promote cellular internalization of FBN-integrin complexes, is reported. The peptide promotes association with MB49 mouse model bladder tumor cells in a sequence-specific and concentration-dependent manner, with the maximum cell association occurring at 2 mol % RWFV-PEG2000-DSPE. Double PEGylation of the liposome membrane (i.e., 4 mol % mPEG1000-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…We anticipate that this interaction will prevent loss of vehicle from the bladder tumor sites due to the urine influx and bladder voiding. Previously, we have reported that empty Cy5.5 labelled liposomes displaying the RWFV targeting peptide was able to associate with murine bladder cancer cells (MB49) is a sequence specific manner 28. Unfortunately, those dispersions were prepared using sonication and extrusion techniques, making it impossible to achieve the delivery of fragile nucleic acid payloads in a functional manner.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We anticipate that this interaction will prevent loss of vehicle from the bladder tumor sites due to the urine influx and bladder voiding. Previously, we have reported that empty Cy5.5 labelled liposomes displaying the RWFV targeting peptide was able to associate with murine bladder cancer cells (MB49) is a sequence specific manner 28. Unfortunately, those dispersions were prepared using sonication and extrusion techniques, making it impossible to achieve the delivery of fragile nucleic acid payloads in a functional manner.…”
Section: Resultsmentioning
confidence: 99%
“…The alkyne modification on the peptide was utilized for a copper-catalyzed azide−alkyne cycloaddition (CuAAC) conjugation to DSPE-PEG2k-Azide. A detailed description of the method has been reported previously 28…”
Section: Methodsmentioning
confidence: 99%
“…The endocytosis ability of liposomes is essential for cancer therapeutic efficacy. Previous studies have revealed the importance of internalization to increase the nanoparticle cytotoxicity efficacy against liquid tumors [ 22 , 23 ]. Sapra provided evidence showing that using internalizing anti-CD19-immunoliposomes compared with non-internalizing anti-CD20-immunoliposomes significantly improved the therapeutic outcome, prolonging the lifespan of Namalwa cell-bearing mice ( P < 0.001) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The endocytosis ability of liposomes is essential for cancer therapeutic e cacy. Previous studies have revealed the importance of internalization ability to increase the nanoparticle cytotoxicity e cacy against liquid tumors [23,24]. Sapra provided evidence which showed that using internalizing anti-CD19immunoliposomes compared with the non-internalizing anti-CD20-immunoliposomes signi cantly improved the therapeutic outcome, prolonging the lifespan of Namalwa cell-bearing mice (P < 0.001) [25].…”
Section: Discussionmentioning
confidence: 99%